Mapping Subsurface and Surface Characteristics of the Recent Pesanggrahan Landslide, Central Java, Indonesia, for Landslide Hazard Management - Anastasia Neni Candra Purnamasari; Eddy Hartantyo; Junun Sartohadi; Hazqial Hafazhah (Environment and Natural Resources Journal)
Regions prone to deep landslides are characterized by thick materials exceeding 10 m and frequent natural disasters. This research aims to analyze the recent occurrence of Pesanggrahan landslide in Central Java, Indonesia, which is a region consisting of both settlements and rice fields. Surface mapping was conducted using aerial photos and direct field observations. Additionally, subsurface conditions to identify the unconsolidated material layers below the landslide surface have been analyzed using the seismic refraction method. The primary velocity (Vp) values are represented in 2D subsurface cross sections. Differences in Vp values corresponded to different geological layers. There were four distinct layers: Top Soil (TS), Clay (CL), Weathered Bedrock (WB), and Tuff Breccia (TB) within the 2D seismic refraction cross-section with Vp values ranging from 150 to 1,800 m/s. The ranges of Vp are: 150-600 m/s for Top Soil (TS), 600-1,200 m/s for Clay (CL), 1,200-1,800 m/s for Weathered Bedrock (WB), and values exceeding 1,800 m/s for Tuff Breccia (TB). The material layer is critical for sustainable land management strategies aimed to control landslides. Furthermore, the potential depth of the sliding plane was managed through effective environmental management practices, including proper disposal of household waste and minimizing the cutting of steep slopes.